Divide to conquer: A complex pattern of biodiversity depicted by vertebrate components in the Brazilian Atlantic Forest - Silva, Sofia Marques; Moraes-Barros, Nadia; Ribas, Camila Cherem; Ferrand, Nuno; Morgante, João Stenghel (Biological Journal of the Linnean Society, 2012)
The identification of northern and southern components in different vertebrate species led researchers to accept a two-component hypothesis for the Brazilian Atlantic forest (BAF). Nevertheless, neither a formal proposal nor a meta-analysis to confirm this coincidence was ever made. Our main objective here was therefore to systematically test in how many vertebrate components the BAF could be divided by analysing existing empirical data. We used two approaches: (1) mapping and comparing the proposed areas of vertebrate endemism in the BAF and (2) analysing studies mentioning spatial subdivisions in distinct forest-dependent vertebrates within the biome, by the use of panbiogeography. The four large-scale endemism area components together with the six small-scale panbiogeographical ones allowed the definition of three BAF greater regions, subdivided into nine vertebrate components, latitudinally and longitudinally organized. Empirical time estimates of the diversification events within the BAF were also reviewed. Diversification of these vertebrates occurred not only in the Pleistocene but also throughout the Miocene. Our results confirm the BAF's complex history, both in space and time. We propose that future research should be small-scale and focused in the vertebrate components identified herein. Given the BAF's heterogeneity, studying via sections will be much more useful in identifying the BAF's historical biogeography. © 2012 The Linnean Society of London.
Keywords: Biodiversity; Biome; Complexity; Endemism; Geographical Distribution; Heterogeneity; Meta Analysis; Miocene; Phylogeny; Phylogeography; Pleistocene; Species Diversity; Taxonomy; Vertebrate; Vicariance; Atlantic Forest